Возрастной состав и сезоны забоя северного оленя в хозяйственной деятельности населения Надымского городка в XVII-XVIII вв. - Bachura, O. P.; Бачура, О. П. (Издательство Тюменского государственного университета, 2016)
Nadym is a town in Yamalo-Nenets Autonomous Okrug, located on the Nadym River. This work describes the results of determination of age composition and seasons of reindeer slaughter at the end of the XVI – the beginning of the XVIII century. Determination of these parameters is based on analysis of growth layers in teeth of reindeer as well as on analysis of the dental system. It was shown that people slaughtered reindeer mainly in the autumn (October-November). It can be traced in ritual activity as well as in economic activity. Fewer reindeer were killed in summer months. Probably the population was living in the town mainly from autumn to mid-spring. Every summer most of the population left the settlement with reindeer herds and went to the north of the tundra. Probably for food purposes people killed reindeer aged from 1 to 4. For ritual purposes people killed animals aged from six months to 1 year. There were few animals aged from 4 to 8. Perhaps reindeer over the age of 4 were used for transport purposes. The prevalence of certain age groups among the slaughtered animals indicates that the population of the Nadym town at the end of the XVI century had quite numerous domestic reindeer herds. Проведено исследование возрастного состава и сезона забоя северного оленя в хозяйственной деятельности 17-18 вв.